Burnout syndrome, satisfaction, and quality of work life in Chilean public health workers - Salgado-Roa, Jorge Alejandro; Leria-Dulčić, Francisco Jose (Universidad y Salud, 2019)
Introduction: The negative influence of the burnout syndrome (BS) on work performance has been demonstrated. However, data are still elusive regarding its specific relationship with Job Satisfaction (JS) and Professional Quality of Life (ProQOL) in professions associated with public health. Objective: To analyze the association between BS, JS and ProQOL, and some socio-labor variables of 169 Chilean public health professionals. Materials and methods: A comparative cross-sectional associative study that applied the Maslach Burnout Inventory (MBI), the Labor Satisfaction Scale (S20/23), and the Professional Life Questionnaire (PLQ-35). Results: 10% of participants perceived high BS levels and satisfactory HS and ProQOL, while 88.8% of health professionals acknowledged medium/moderate levels. 33.5% of the variability in Emotional Fatigue could be explained by chronological age, Intrinsic Motivation, Management Support, marital status and years of service. Good BS predictors are suggested. Conclusions: The data reflect a medium/moderate prevalence of BS, which can be understood in light of the insidious influence of this syndrome. Chronological age and marital status are suggested as protective factors. The results are discussed in the context of current literature.